Supervision of Law Enforcement Authority Through Pre-Trial in the 2025 Criminal Code - Muhammad Yasir (West Science Law and Human Rights, 2025)
This study aims to analyze whether the 2025 Criminal Procedure Code (KUHAP) has addressed the substantive weaknesses of pretrial proceedings, how law enforcement authorities are monitored through pretrial proceedings in the 2025 Criminal Procedure Code, and how pretrial proceedings differ from those in the 2025 Criminal Procedure Code (KUHAP) with Habeas Corpus in the UK and Rechter Commissioner in the Netherlands. This research is descriptive, using a statutory, conceptual, and comparative legal approach. It utilizes secondary data and is analyzed qualitatively. The results indicate that: 1) Substantially, the 2025 Criminal Procedure Code has attempted to address the weaknesses of pretrial proceedings, namely by expanding the scope and strengthening the pretrial mechanism, with the exception of the still unclear third party, the focus of the examination, and the procedural law used. 2) Supervision of law enforcement authorities through pretrial proceedings in the 2025 Criminal Procedure Code The scope of pretrial proceedings has expanded, with the addition of: suspect determination, searches, seizures, wiretapping, letter inspection, blocking, travel bans, unrelated seizures, case delays, and suspensions. Weaknesses include: a) Coercive measures authorized by the Chief Justice are excluded from pretrial proceedings. b) New pretrial proceedings have not been specifically regulated, and c) the examination of suspects/witnesses/victims is not included in pretrial proceedings. 3) Habeas Corpus only focuses on assessing the validity of a person's detention. The Rechter Commissioner focuses on broad oversight of investigators' actions prior to the investigation (pre-trial), while pretrial proceedings focus on a broad examination and are assessed after the action has been taken (post factum).